2021
DOI: 10.1002/cac2.12184
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transcription factor A plays opposite roles in the initiation and progression of colitis‐associated cancer

Abstract: Background Mitochondria are key regulators in cell proliferation and apoptosis. Alterations in mitochondrial function are closely associated with inflammation and tumorigenesis. This study aimed to investigate whether mitochondrial transcription factor A (TFAM), a key regulator of mitochondrial DNA transcription and replication, is involved in the initiation and progression of colitis‐associated cancer (CAC). Methods TFAM expression was examined in tissue samples of inflammatory bowel diseases (IBD) and CAC by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…TFAM is necessary for transcription and replication of mtDNA, which encodes proteins involved in electron transport chain (ETC), whose defects always induce extensive metabolic changes in TCA cycle. Previously, we found that TFAM plays a crucial regulatory role in mitochondrial energy metabolism in tumor cells (Huang et al , 2014; Wen et al , 2019; Yang et al , 2021). In addition, previous studies have also reported the role of TFAM deficiency in disturbing TCA cycle.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…TFAM is necessary for transcription and replication of mtDNA, which encodes proteins involved in electron transport chain (ETC), whose defects always induce extensive metabolic changes in TCA cycle. Previously, we found that TFAM plays a crucial regulatory role in mitochondrial energy metabolism in tumor cells (Huang et al , 2014; Wen et al , 2019; Yang et al , 2021). In addition, previous studies have also reported the role of TFAM deficiency in disturbing TCA cycle.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, only TFAM LKO mice rapidly and stably developed lung metastases, suggesting that mitochondrial dysfunction induced by TFAM loss, but not by deregulation of mitochondrial morphology, has a strong ability to drive tumor metastasis. As the key regulator of mtDNA replication and transcription, TFAM has been reported to be deeply involved in metabolic reprogramming and proliferation of tumor cells (Woo et al , 2012; Huang et al , 2014; Yang et al , 2021). Moreover, TFAM expression is a prognostic factor for survival in endometrial carcinomas and colorectal cancer patients with tumor metastasis (Toki et al , 2010; Yoshida et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are integral in tumorigenesis given that multiple aspects of mitochondrial functions, including metabolism, oxidative stress regulation, cell death susceptibility and signaling, are involved in tumorigenesis [ 9 , 43 ]. Accumulating evidence indicates that PPR proteins can play an important role in mitochondria [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria provide most of the biological energy for the activities of organisms and are important production sites of catabolism of organisms, as well as key regulatory factors of cell proliferation and apoptosis ( 8 ). Mitochondrial dysfunction is closely related to many congenital diseases, inflammation, and tumors ( 9 , 10 ). In tumors, mitochondria are key factors in tumor progression.…”
Section: Introductionmentioning
confidence: 99%